Identification and Expression Analysis of Medicago truncatula Isopentenyl Transferase Genes (IPTs) Involved in Local and Systemic Control of Nodulation - Azarakhsh, Mahboobeh; Lebedeva, Maria A.; Lutova, Lyudmila A. (Frontiers in Plant Science, 2018)
Cytokinins are essential for legume plants to establish a nitrogen-fixing symbiosis with rhizobia. Recently, the expression level of cytokinin biosynthesis IPTs (ISOPENTENYLTRANSFERASES) genes was shown to be increased in response to rhizobial inoculation in Lotus japonicus, Medicago truncatula and Pisum sativum. In addition to its well-established positive role in nodule primordium initiation in root cortex, cytokinin negatively regulates infection processes in the epidermis. Moreover, it was reported that shoot-derived cytokinin inhibits the subsequent nodule formation through AON (autoregulation of nodulation) pathway. In L. japonicus, LjIPT3 gene was shown to be activated in the shoot phloem via the components of AON system, negatively affecting nodulation. However, in M. truncatula, the detailed analysis of MtIPTs expression, both in roots and shoots, in response to nodulation has not been performed yet, and the link between IPTs and AON has not been studied so far. In this study, we performed an extensive analysis of MtIPTs expression levels in different organs, focusing on the possible role of MtIPTs in nodule development. MtIPTs expression dynamics in inoculated roots suggest that besides its early established role in the nodule primordia development, cytokinin may be also important for later stages of nodulation. According to expression analysis, MtIPT3, MtIPT4 and MtIPT5 are activated in the shoots in response to inoculation. Among these genes, MtIPT3 is the only one the induction of which was not observed in leaves of the sunn-3 mutant defective in CLV1-like kinase, the key component of AON, suggesting that MtIPT3 is activated in the shoots in an AON-dependent manner. Taken together, our findings suggest that MtIPTs are involved in the nodule development at different stages, both locally in inoculated roots and systemically in shoots, where their expression can be activated in an AON-dependent manner.